Study of Chlorella vulgaris Density and Growth Rate at Different Effluent Concentrations - Siti Siwi Wulandari; Tri Retnaningsih Soeprobowati; Kismartini Kismartini (Buletin Oseanografi Marina, 2026)
Household wastewater processing at the Communal Wastewater Treatment Plant (WWTP) operated by the Guyub Rukun Community in Tegalsari Hamlet, Salatiga City, Indonesia, is expected to reduce water pollution in the Cengek River. However, effluent testing revealed high concentrations of TP, COD, and BOD. This study aims to conduct laboratory-scale phycoremediation experiments using Chlorella vulgaris with media mixed using Communal WWTP effluent. Samples were taken from the outlet pipe to obtain household wastewater treatment effluent. Sampling was done using the grab sampling method at 2 PM during high sanitation activity. Based on laboratory tests, the highest Chlorella vulgaris density for 0% effluent concentration was 77.75 x 104 cells/mL (day 7), 66.13 x 104 cells/mL (day 6) in 20%, 126.13 x 104 cells/mL (day 7) in 40%, 69.38 x 104 cells/mL (day 6) in 60%, 188.88 x 104 cells/mL (day 6) in 80%, and 232 x 104 cells/mL (day 7) in 100%. The best growth rate at 0% effluent concentration was 3.87 cells/mL/day (day 6), 3.52 cells/mL/day (day 6) in 20%, 4.25 cells/mL/day (day 6) in 40%, 3.56 cells/mL/day (day 5) in 60%, 4.69 cells/mL/day (day 6) in 80%, and 4.99 cells/mL/day (day 7) in 100%. The results showed that Chlorella vulgaris's best density and growth rate was 100% effluent concentration. This indicates that the WWTP effluent's TP, TN, and Nitrate contents can be a good substitute for microalgae chemical fertilizers. This study also demonstrated that Chlorella vulgaris is in effective phycoremediation agent and can grow in high concentrations of WWTP effluent.